ANALISIS YURIDIS PENARIKAN DUKUNGAN TERHADAP CALON TERDAFTAR OLEH PDIP TERHADAP CALON TERDAFTAR PILKADA LAMPUNG TIMUR - Sofyan Wegi Alfariki; Adi Iskandar (Legal Studies Journal, 2025)
This study examines the dynamics of the Indonesian Democratic Party of Struggle (PDIP) withdrawing its support for the candidate pair running for regent and vice-regent in the 2024 Lampung Timur Regional Election. The primary focus of the research is to analyze the reasons behind PDIP's decision to revoke its endorsement of Ela Siti Nuryamah and Azwar Hadi, as well as the impact of this decision on the democratic process in the region. The study adopts a normative juridical approach, analyzing relevant legislation, particularly PKPU Regulation No. 8 of 2024, which prohibits the withdrawal of support after registration. The findings reveal that concerns among its cadres and constituents opposing the possibility of an uncontested election influenced PDIP's decision. This withdrawal of support not only sparked controversy among the public but also raised questions about the integrity and commitment of political parties in the regional election process. This research aims to contribute to a better understanding of local political dynamics and the legal implications of political party actions in the context of regional elections.